(untitled) (Archive of Conferences, 2021)
The article describes the procedure for organizing the accounting of costs for the implementation of rationalization proposals, considered as one of the elements of innovation potential. The article provides a definition of the concept of "rationalization proposal"; the procedure for organizing accounting of costs for the implementation of rationalization proposals has been substantiated; the corresponding accounting records are presented; provides a list of registers and primary documents that form the basis of the accounting system.